Peran Literasi Digital Dalam Pembelajaran Sejarah - fathulaila, fathulaila (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Type This study explores the role of digital literacy in history education within the global era, emphasizing its relevance in addressing educational challenges in the digital age. The research aims to analyze how digital literacy enhances historical learning through digital resources such as online archives, virtual museums, and social media. Using a qualitative method with a literature review approach, data was collected from journals, books, and online sources. The findings reveal that digital literacy facilitates information access and fosters critical thinking, analytical skills, and a deeper understanding of historical values. Tools like virtual tours effectively boost students’ interest in history, reinforce national identity, and instill global perspectives. This study underscores the importance of equipping educators and students with digital literacy skills to create meaningful and engaging history learning experiences.